2017
DOI: 10.1002/2017gl074606
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal Scale Detection Time for Potentially Increasing Atlantic Storm Surges in a Warming Climate

Abstract: Storm surges are key drivers of coastal flooding, which generate considerable risks. Strategies to manage these risks can hinge on the ability to (i) project the return periods of extreme storm surges and (ii) detect potential changes in their statistical properties. There are several lines of evidence linking rising global average temperatures and increasingly frequent extreme storm surges. This conclusion is, however, subject to considerable structural uncertainty. This leads to two main questions: What are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 19 publications
3
27
2
Order By: Relevance
“…Knighton et al 2017, Arns et al 2013. Additionally, previous studies have demonstrated the difficulties in making robust modeling choices using a GEV/block maxima approach (Ceres et al, 2017;Lee et al, 2017). These relative strengths/weaknesses of the GEV versus PP/GPD approaches motivate the present study to focus on constraining uncertainties within the PP/GPD model.…”
Section: Introductionmentioning
confidence: 95%
“…Knighton et al 2017, Arns et al 2013. Additionally, previous studies have demonstrated the difficulties in making robust modeling choices using a GEV/block maxima approach (Ceres et al, 2017;Lee et al, 2017). These relative strengths/weaknesses of the GEV versus PP/GPD approaches motivate the present study to focus on constraining uncertainties within the PP/GPD model.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have provided important new insights by examining the potentially sizable impacts of non-stationarity in the treatment of storm frequency, distribution and intensity (e.g. Ceres et al 2017, Lee et al 2017, Cid et al 2016, Grinsted et al 2013, Haigh et al 2010b, Menéndez and Woodworth 2010. For example, Grinsted et al (2013) use a generalized extreme value (GEV) distribution to model extreme sea levels, and incorporate non-stationarity in the model parameters by allowing them to covary with global mean surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Another option is to process data to achieve independence, then use shorter time lengths of blocks (Grinsted et al 2013), but the choice of processing procedure is nontrivial and the fidelity with which non-stationary behavior may be detected is uncertain (e.g. Ceres et al 2017, Lee et al 2017. The PP/GPD modeling approach is an attractive option because all events above a specified threshold are considered in fitting the model, leading to a richer set of data (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, estimated base flood levels or dike heights do not allow city planners to evaluate changes to damage associated with surge heights above the selected return level. Additionally, return periods for these estimated levels are typically long compared to the record of surge observations available (Grinsted et al, 2012(Grinsted et al, , 2013Menéndez and Woodworth, 2010;Ceres et al, 2017;Lee et al, 2017). This relative sparsity of data leads to large uncertainties surrounding estimates of long-period return levels (Coles, 2001) and the potential for bias in estimating extreme event risks using common extreme value analysis methods (Coles et al, 2003;Ceres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%